Pituitary Dysfunction After Traumatic Brain Injury: A Clinical and Pathophysiological Approach - Fatih Tanrıverdi; Harald J. Schneider; Gianluca Aimaretti; Brent E. Masel; Felipe F. Casanueva; Fahrettin Keleştimur (2015)
Traumatic brain injury (TBI) is a growing public health problem worldwide and is a leading cause of death and disability. The causes of TBI include motor vehicle accidents, which are the most common cause, falls, acts of violence, sports-related head traumas, and war accidents including blast-related brain injuries. Recently, pituitary dysfunction has also been described in boxers and kickboxers. Neuroendocrine dysfunction due to TBI was described for the first time in 1918. Only case reports and small case series were reported until 2000, but since then pituitary function in TBI victims has been investigated in more detail. The frequency of hypopituitarism after TBI varies widely among different studies (15–50% of the patients with TBI in most studies). The estimates of persistent hypopituitarism decrease to 12% if repeated testing is applied. GH is the most common hormone lost after TBI, followed by ACTH, gonadotropins (FSH and LH), and TSH. The underlying mechanisms responsible for pituitary dysfunction after TBI are not entirely clear; however, recent studies have shown that genetic predisposition and autoimmunity may have a role. Hypopituitarism after TBI may have a negative impact on the pace or degree of functional recovery and cognition. What is not clear is whether treatment of hypopituitarism has a beneficial effect on specific function. In this review, the current data related to anterior pituitary dysfunction after TBI in adult patients are updated, and guidelines for the diagnosis, follow-up strategies, and therapeutic approaches are reported.